Determinants of blood pressure control: a survey on Cilnidipine–Telmisartan use in uncontrolled hypertension - Khanna, Suresh K.; Kubihal, Suraj S.; Hassan, Haji J. U.; Thirumalai, Sreekumar; Bajaj, Supriya; Choudhary, Balaram; Kumar, Karthik; Srivastava, Rachit; Singh, Rahul K.; Patel, Lalibhai A.; Suresh, Manjula; M., Krishna Kumar (International Journal of Research in Medical Sciences, 2026)
Background: Uncontrolled hypertension remains a major public health challenge, often complicated by poor medication adherence and multiple comorbidities. Fixed-dose combinations such as Cilnidipine and Telmisartan (CILTEL) have been proposed to improve blood pressure (BP) control through complementary mechanisms and simplified dosing. Objectives were to assess physicians’ perceptions, attitudes, and prescribing patterns regarding CILTEL in the management of uncontrolled hypertension, and to identify factors associated with achieving ≥80% BP reduction. Methods: A cross-sectional, questionnaire-based survey was conducted among 788 physicians across various regions and practice settings. Data were collected via structured personal interviews. Descriptive statistics summarized demographic and professional characteristics. Multivariate logistic regression identified independent predictors of achieving ≥80% BP reduction. Results: The majority of physicians reported high satisfaction with CILTEL for patients with uncontrolled hypertension, citing improved BP control and better adherence as key benefits. Multivariate analysis revealed that good patient adherence (OR=1.91), absence of major comorbidities (OR=2.03), and longer duration of therapy (OR=1.83) were significant predictors of BP target achievement. Physicians also highlighted the convenience of a fixed-dose regimen in reducing pill burden and enhancing patient compliance. Conclusions: CILTEL is perceived by physicians as an effective and well-tolerated option for uncontrolled hypertension, particularly when adherence is optimized and comorbidity burden is low. Its fixed-dose nature supports improved compliance, potentially translating into better long-term cardiovascular outcomes.